Pemberdayaan UMKM Desa Kadumaneuh Kecamatan Banjar Kabupaten Pandeglang melalui pelatihan dan fasilitasi merek - Endang Purwaningsih; Irwan Santosa; Irfan Islami (IKIP SILIWANGI, 2024)
The stakeholders in this program are MSMEs, the Village Head along with the village apparatus (village officials) of Kadumaneuh, representatives from the Village-Owned Enterprises (BUMDesa), and the community. The issues faced by the stakeholders include: (1) lack of knowledge about business legality, especially trademarks, (2) weak entrepreneurial spirit, (3) no MSMEs with registered trademarks and no training or facilitation for trademark legality, (4) suboptimal role of BUMDesa, (5) absence of MSME associations, (6) absence of Village Cooperatives, (7) absence of CSR programs or similar initiatives facilitating business legality. So, both the legal entity and the legal product of the stakeholders are still lacking. Due to the multitude of stakeholder issues, the addressed problems are (1) efforts to increase stakeholders' knowledge and motivation in acquiring business legality, especially trademarks, and (2) 2) Partner's efforts to prepare the complete legality of brand registration in accordance with the priority scale that partners and the Team have justified during the needs assessment. The objectives of this program are (1) so that partners in general increase the knowledge and motivation of partners in obtaining business legality, especially brand registration, while also being able to develop the business climate in Kadumaneuh Village, and (2) so that partners are able to prepare complete legality for brand registration according to the priority scale of partners and the team has been justified. This activity is conducted using persuasive and participatory action methods. After training and mentoring, regarding the issue of Empowering MSMEs in Kadumaneuh Village, Banjar Subdistrict, Pandeglang Regency Through Trademark Training and Facilitation, it has been well addressed through continuous counseling and mentoring, and the average increase in activities of Empowering MSMEs in Kadumaneuh Village, Banjar Subdistrict, Pandeglang Regency Through Trademark Training and Facilitation is 29.1%.